Paradox between Public Transport and Private Car as a Modal Choice in Policy Formulation - Anwar, AHM Mehbub (Journal of Bangladesh Institute of Planners, 2012)
This paper presents the stance towards modal choice behavior between public transport and private car. To find out the probable solutions, this paper investigated the latent attitudes of the trip makers concerning modal choice between private car and public transport and the advantages and disadvantages of these two modes as a choice. It was also discussed in this paper that the public transport usage can be increased if the service of public transport is designed in a way that accommodates the level of services required by the customers. Even though, several factors, such as individual characteristics and lifestyle, the type of journey, length of trip, the apparent service performance etc. of each transport mode play the significant role for the modal choice in the transport sector. It was also focused in this paper that the influence of car usage should be targeted to reduce car usage. DOI: http://dx.doi.org/10.3329/jbip.v2i0.9568 Journal of Bangladesh Institute of Planners Vol. 2, December 2009, pp. 71-77